Inhibitory effect of chlorogenic acid extract from peach blossoms on growth of Monilinia fructicola - WANG Haijing; ZHANG Man; LI Haiping; WU Meilan; LIU Chunsheng; SU Kai; ZHANG Chenguang; MENG Dong; YANG Qing; SUPRUN Ivan Ivanovich; WU Junkai (Guoshu xuebao)
[Objective] Brown rot is a destructive disease in peach production, which directly threatens the sustainable development of peach industry. This disease not only causes fruit spoilage, but also leads to significant economic losses during postharvest storage and transportation. This has become a critical bottleneck restricting the quality improvement, efficiency enhancement, and market competitiveness in the peach industry. Chlorogenic acid (CGA) is a phenolic secondary metabolite, a phenylpropanoid synthesis synthesized by shikimic acid pathway during respiration of plants, and exists in different tissues of most Rosaceae fruit trees. Chlorogenic acid demonstrates antimicrobial activity to a variety of pathogenic species, including bacteria and fungi, and the extraction and research of chlorogenic acid have become a hot spot in the study on natural extracts. In this study, the extraction efficiency of CGA from three peach strains with distinct flower colors (red, pink and white) was systematically investigated, and the inhibitory effect of these CGA extracts and chlorogenic acid standard on growth of Monilinia fructicola, a major pathogen of peach brown rot, was evaluated. The results are expected to provide scientific basis for the comprehensive utilization of peach blossom resource and the development of eco-friendly strategies for brown rot disease control. [Methods] Peach blossoms were picked from different peach strains with distinct flower colors, including R-2(red flower), P-3(pink flower), and W-7(white flower). Fresh peach flower petals were dried in an oven at 42℃to a constant weight, and then crushed into powder. CGA was extracted from dried peach flower powder using an ultrasound-assisted methanol extraction method. The key extraction parameters, such as solid-to-liquid ratio (1∶10, 1∶20, and 1∶30), methanol concentration (60%, 70%, and 80%), ultrasonic power (200 W), extraction temperature (40℃), and extraction time (60 min), were systematically optimized through the single-factor experiment. Two extraction cycles were performed to maximize the yield. The CGA content in the extracts was quantified via the high performance liquid chromatography (HPLC) under the following chromatographic conditions: a C18 column, gradient elution with 0.1% formic acid (mobile phase A) and methanol (mobile phase B), flow rate of 1 mL·min-1, detection wavelength of 280 nm, and injection volume of 20 μL. The fungal infection assay on peach callus tissues was conducted in the early stage of this study. The results showed that the white mycelium (pathogen of peach brown rot) could be firmly attached to the surface of the peach callus tissues, and the color of the peach callus began to change from normal color to brown or dark brown color. The texture of the tissue also changed, from relatively dense to soft status, stained by water. The pathogens had obvious ability to infect callus and maintained good radial growth ability on the surface of callus. At the same time, the strain was identified as M. fructicola. The antifungal activity of the extracts was assessed through in vitro inhibition assays. M. fructicola was cultured on potato dextrose agar (PDA) medium, and mycelium plugs (7 mm diameter) were treated with varying concentrations of CGA extracts (0.2, 0.3 or 0.4 mg·mL-1) or chlorogenic acid standard. The control group received PDA only. Mycelium growth was monitored for 5 days, and inhibition rates were calculated using the formula below: Inhibition rate/%=[(Dcontrol-Dplug)-(Dtreatment-Dplug)/Dcontrol-Dplug]×100, where Dplug, Dcontrol and Dtreatment represent plug diameter, control colony diameter, and treated colony diameter, respectively. By observing the fungus growth and the inhibition rate of pathogenic fungus, the inhibition of chlorogenic acid standard and peach blossom extracts with different concentrations on peach brown rot fungus was judged. [Results] Under optimized conditions (ratio of solid to liquid 1∶10, 80% methanol, 200 W ultrasonic power, 40℃, 60 min, and 2 cycles), the CGA contents in red (R-2), pink (P-3), and white (W-7) peach blossom extracts were 0.44, 0.324, and 0.417 mg·mL-1, respectively. By HPLC analysis and comparison with the peak time of chlorogenic acid standard, chlorogenic acid was identified as the main phenolic compound in the peach blossom extract. In vitro antifungal assays demonstrated dose-dependent and time-dependent inhibition of M. fructicola. After 5 days of treatment at a concentration of 0.3 or 0.4 mg·mL-1, both CGA standard and peach blossom extracts showed the greatest inhibitory effect, significantly reducing mycelial expansion compared to control (p<0.001), and the inhibition rates of red, pink, and white strain extracts were 34.65%, 21.47%, and 21.38%, respectively, highlighting the inhibitory efficacy of three peach blossom extracts. The inhibitory effects showed the same trend as the extraction effects of chlorogenic acid from red, pink and white peach blossoms. Notably, lower concentrations (0.2 mg·mL-1) also showed measurable inhibition, although less pronounced. Morphological observation showed that mycelial integrity was destroyed and sporulation was inhibited in the treatment group, which was consistent with quantitative data. [Conclusion] In this research, the ultrasonic assisted methanol extraction method of chlorogenic acid extracted from peach blossom was successfully established and optimized. The content of chlorogenic acid was the highest when the ratio of solid to liquid was 1∶10 and the concentration of extraction solvent was 80% methanol. The extracts demonstrated antifungal activity against M. fructicola, underscoring their potential as natural alternatives to synthetic fungicides. These findings not only advance the understanding of peach blossom phytochemistry but also offer practical insights for valorizing agricultural by-products and mitigating postharvest losses caused by brown rot. Future research should focus on field trials, mechanism elucidation (e.g., oxidative stress induction), and synergistic combinations with other bioactive compounds to enhance commercial applicability.